A novel ENAM mutation causes hypoplastic amelogenesis imperfecta. (4th May 2021) - Yu, Shunlan; Zhang, Chenying; Zhu, Ce; Quan, Junkang; Liu, Dandan; Wang, Xiaozhe; Zheng, Shuguo
Abstract: Objectives: To identify the genetic cause of one Chinese family with hypoplastic amelogenesis imperfecta (AI) and explore the relationship between genotype and its phenotype. Material and Methods: One Chinese family with generalized hypoplastic AI was recruited. One deciduous tooth from the proband was subjected to scanning electron microscopy. Whole‐exome sequencing was performed and identified mutation was confirmed by Sanger sequencing. Bioinformatics studies were further conducted to analyze potential deleterious effects of the mutation. Results: The proband presented a typical hypoplastic AI phenotype whose teeth in deciduous and permanent dentitions showed thin, yellow, and hard enamel surface. The affected enamel in deciduous tooth showed irregular, broken, and collapsing enamel rods with borders of the enamel prisms undulated and structural shapes of prisms irregular. A novel homozygous nonsense mutation in the last exon of the enamelin (ENAM) gene (NM_031889.3; c.2078C>G) was identified in the proband, which was predicted to produce a highly truncated protein (NP_114095.2; p.(Ser693*)). This mutation was also identified in the proband's parents in heterozygous form. Surprisingly, the clinical phenotype of the heterozygous parents varied from a lack of penetrance to mild enamel defects. Additional bioinformatics studies demonstrated that the detected mutation could change the 3D structure of the ENAM protein and severely damaged the function of ENAM. Conclusion: The novel homozygous ENAM mutation resulted in hypoplastic AI in the present study. Our results provide new genetic evidence that mutations involved in ENAM contribute to hypoplastic AI.